2010
DOI: 10.1587/transinf.e93.d.1878
|View full text |Cite
|
Sign up to set email alerts
|

BioEncoding: A Reliable Tokenless Cancelable Biometrics Scheme for Protecting IrisCodes

Abstract: SUMMARYDespite their usability advantages over traditional authentication systems, biometrics-based authentication systems suffer from inherent privacy violation and non-revocability issues. In order to address these issues, the concept of cancelable biometrics was introduced as a means of generating multiple, revocable, and noninvertible identities from true biometric templates. Apart from BioHashing, which is a two-factor cancelable biometrics technique based on mixing a set of tokenized userspecific random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…The transformation process of BioEncoding, illustrated in Fig. 1, can be summarized in the following steps [8]:…”
Section: Bioencoding Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The transformation process of BioEncoding, illustrated in Fig. 1, can be summarized in the following steps [8]:…”
Section: Bioencoding Overviewmentioning
confidence: 99%
“…Regarding the diversity requirement, it is possible to generate a large number of different BioCodes especially for large address words since 2 2 m different random sequences can be generated using address words of length m. For the non-invertibility requirement, the many-to-one nature of the transformation process can guarantee its irreversibility. In [8], it has been shown that BioEncoding is robust against the brute-force search attacks.…”
Section: Bioencoding Overviewmentioning
confidence: 99%
See 3 more Smart Citations